Hukum Ketenagakerjaan Di Era Digital: Kompatibilitas Peraturan Perundang-Undangan Terhadap Praktik Digital Workplace - Widiastiani, Nindry Sulistya (Fakultas Hukum Universitas Mataram, 2024)
As communication and information technology developed and pushed by the covid-19 pandemic, the digital workplace is becoming a trend among employers. The digital workplace is a way of doing work outside the workplace. Thus, workers can do their jobs outside the company building. The workers use email, instant messaging, social media, cloud, and virtual meeting tools. This practice would affect the work relation situation in their company. This article aims to analyze whether Indonesian labour laws nowadays have been able to accommodate digital workplace practices. The result shows that digital workplace practices would affect at least four essential aspects of the work relation, which are: (1) work time and rest time; (2) occupational health and safety and workers’ social security; (3) freedom of association; and (4) industrial relation dispute settlement. Indonesian labour law is still incompatible with digital workplace practices regarding those four aspects.